PENGEMBANGAN MEDIA AJAR MATEMATIKA MATERI PERKALIAN BERBENTUK MUVIZU PADA SISWA KELAS III SEKOLAH DASAR - Tiasari siregar (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This development study aims to design and develop mathematics teaching media on multiplication material for third grade elementary school students. The method used in this study is Research and Development using the ADDIE model. With its phases starting with the needs, then design, then make teaching media in the form of muvizu, then tested using the last questionnaire revision. In line with the results of trials and revisions, the results of the study explain that the teaching media in the form of muvizu that has been developed has received achievements worthy of use in the process of learning mathematics, especially multiplication material in class.